Adaptación de 14 variedades de maíz tropical de madurez precoz e intermedio de grano amarillo duro introducidas en E.E. El Porvenir Juan Guerra, San Martín - Huanambal Vásquez, César Eloy (2010)
This research work was conducted in the field of the agricultural Experimental Station "El Porvenir", in the Valley of the low may, San Martin province, geographically characterized by the following coordinates: longitude 76 ° 21'15 "and 6 ° 36'15 ' of South latitude and 330 m. s. n. m. m., with the objective of evaluating the greater potential of yield maize variety and adequate agronomic characteristics in March under rainfed conditions and perform economic analysis of the best treatments. Assessed the performance and features vegetative complementary to using statistical design of blocks totally at random (OBCA), with 16 treatments and 3 replicates, whose results were analyzed by analysis of variance and Duncan multiple significance testing. The distancing of planting was 0.80 m between rows and 0.20 m between plants, composting was used using the dose of 120-100-80 Kg of NPK / implemented the SO % of nitrogen together with the f6sforo and potassium 1 or days after sowing and 50% of remaining nitrogen at 30 days after sowing and receiving a total precipitation during the growing period of 460 mm , with an average temperature of 27° C. Of the results obtained according to the statistical analysis, it was concluded; There is a significant statistical difference with treatments in the yield at 14% of moisture with yields fluctuate enters 4 200 and 2 500 Kg / has which corresponds to the variety PHRAPHUTTABAT OS 031 and INIA-602 the highest and lowest respectively. According to agronomic characteristics evaluated and the benefit/cost relationship, determined the PHRAPHUTTABAT variety SO 031, how promising in good yield potential and profitable, with net profits exceeding the 400 new soles, per hectare production.